Analysis of Healthcare Service Quality Based on Patient Satisfaction at Ghaniya Clinic, Medan - Nurliati Nurliati; Reny Juliana Sihombing (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Healthcare service quality is a critical determinant of patient satisfaction and clinic performance, particularly in primary healthcare settings in developing countries. Patient satisfaction serves as a key indicator to assess whether healthcare providers meet patients' expectations and needs. Objective: This study aims to analyze the quality of healthcare services based on patient satisfaction at Ghaniya Clinic, Medan, North Sumatra, Indonesia, using the SERVQUAL model encompassing five dimensions: tangibility, reliability, responsiveness, assurance, and empathy. Methods: A descriptive-analytical cross-sectional study was conducted from September to December 2025. A total of 150 outpatients were recruited using purposive sampling. Data were collected using a validated structured questionnaire based on the SERVQUAL instrument. Descriptive statistics, Customer Satisfaction Index (CSI), and Importance-Performance Analysis (IPA) were employed. Results: The overall patient satisfaction rate was 72.7%. Empathy scored the highest mean satisfaction (3.82 ± 0.51), while tangibility received the lowest score (3.41 ± 0.64). The Customer Satisfaction Index (CSI) was 76.3%, indicating a